Ultrasonic assisted improved dyeing of cellulosic fabric using Vat Blue 4. Issue 1 (2nd January 2020) - Adeel, Shahid; Saeed, Muhammad; Abdullah, Aqsa; Gull Khan, Samreen; Habib, Noman; Kamran, Muhammad; Zuber, Mohammad
ABSTRACT: The need for eco-friendly tool in textile processing is the major concern of consumers and traders. The current study is aimed to use ultrasonic radiation for improvement of Vat dyeing of cellulosic fibers using Vat Blue 4. For this purpose, both fabric and dye solutions were ultrasonically treated for 15–60 min at variable dyeing conditions. Dyeing has been performed onto irradiated and un-irradiated fabrics using irradiated and un-irradiated dye solutions. It is found that good color characteristics are obtained if un-irradiated fabric is dyed at 55 C for 60 min using 50 mL of neutral dye bath. For optimization of vat dyeing conditions, 2.5 mL of sodium dithionite, 2 mL of acetic acid and 2 mL of hydrogen peroxide at redox conditions have been optimized. Organization of International Standards (ISO) standard methods employed onto variable shades for colorfastness show that the Ultrasonic treatment has improved the rating of color characteristics. It is concluded that the Ultrasonic treatment has been proved as a cost- and time-effective tool for Vat dyeing of cellulosic fabric under mild conditions.